EFFECTS OF DIFFERENT PRE-STARTER DIETS ON BROILER PERFORMANCE, GASTRO INTESTINAL TRACT MORPHOMETRY AND CARCASS YIELD - M. S. Ullah; T. N. Pasha; Z. Ali; Saima; F. M. Khattak; Z. Hayat (Journal of Animal and Plant Sciences, 2012)
An experiment was conducted to examine the effects of different pre-starter diets on the performance, digestive organs and carcass characteristics of broilers. One hundred and fifty day-old broiler chicks were divided into five groups with three replicates having ten chicks each. During first ten days the birds were fed on five experimental pre-starter diets formulated with different metabolizable energy (ME; varied from 2750 to 2850 kcal/kg) and different lysine levels (varied from 1.3 to 1.5%) but with same crude protein level (21%). After 10 days single starter and finisher crumble diets were fed to the birds up to 28 and 35 days of age, respectively. Statistical analysis of live weight, feed intake and feed conversion revealed significant differences (P<0.05) among the treatments. Pre-starter diet with ME 2850 kcal/kg and 1.4 % total lysine resulted in optimum performance. Carcass yield, weights of visceral organs and parameters of digestive tract morphometry did not show any significant difference. It may be inferred that a precisely formulated pre-starter diet according to bird’s nutrient requirement could trigger growth. Nevertheless, developments of gastro intestinal tract (GIT) and carcass characteristics are independent of nutritional manipulation in pre-starter diets. However, there is a dire need of further experimentation to explore nutrient requirements of broilers at early age.
Keywords: Broiler; early nutrition; energy; lysine; gastro intestinal tract